Potensi Beauveria bassiana sebagai Agens Hayati Spodoptera litura Fabr. pada Tanaman Kedelai - Ayu Rosmiati; Cecep Hidayat; Efrin Firmansyah; Yati Setiati (Agrikultura, 2018)
ABSTRACTThe Potency of Beauveria bassiana as a biological control agent of Spodoptera lituraThe attack of Spodoptera litura can result in the decrease of soybean yield, so that the soybean production cannot fulfill the demand of soybean. The objective of the study was to examine the potency of Beauveria bassiana as a biological control agent of Spodoptera litura. The research was conducted at the Pest Laboratory, Departement of Agrotechnology, UIN Sunan Gunung Djati Bandung from January to March 2017. The research was carried out using Completely Randomized Design (RBD) with six treatments of B. bassiana spore density and four replications. The treatments were spore densities of 100 (control), 102, 104, 106, 108, and 1010/ml aquades that applied to the instar II of S. litura larvae. The advanced test used was Duncan's advanced test of 5%. The results showed that the B. bassiana density spore of 1010/ml aquades caused the highest S. litura larvae mortality of 82.50% and the lowest weight of food eaten by S. litura larvae of 0.79 g.Keywords: Biocontrol Agent, Beauveria bassiana, Spodoptera litura, SoybeanABSTRAKSerangan Spodoptera litura dapat menurunkan hasil tanaman kedelai, sehingga produksi tanaman kedelai belum bisa memenuhi permintaan kedelai di Indonesia. Tujuan penelitian ini untuk menguji patogenitas Beauveria bassiana sebagai agens hayati pengendali Spodoptera litura. Penelitian dilaksanakan di Laboratorium Hama Jurusan Agroteknologi, UIN Sunan Gunung Djati Bandung dari Januari sampai Maret 2017, menggunakan Rancangan Acak Lengkap (RAL) dengan enam perlakuan kerapatan spora B. bassiana dan empat ulangan. Perlakuan tersebut adalah kerapatan spora 100 (kontrol), 102, 104, 106, 108, dan 1010/ml aquades yang diaplikasikan pada larva S. litura instar II. Uji lanjut yang digunakan adalah Uji lanjut Duncan taraf 5%. Hasil penelitian menunjukkan bahwa kerapatan spora B. bassiana 1010 /ml aquades menyebabkan mortalitas larva S. litura sebesar 82,50% dan bobot pakan yang dimakan oleh larva S. litura paling rendah sebesar 0,79 g.Kata Kunci: Agens hayati, Beauveria bassiana, Spodoptera litura, Kedelai